Pengaruh Pembelajaran Berdiferensiasi Melalui Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Pemecahan Masalah dan Hasil Belajar Ipas Siswa Kelas V SD Negeri Borongkaramasa Kab. Gowa - Hapsah, Hapsah; Nurlina, Nurlina; Syamsuddin, Agustan (Jurnal Ilmiah Global Education, 2025)
This study aims to determine the effect of differentiated learning through guided inquiry model on problem-solving ability and science learning outcomes of fifth grade students of SD Negeri Borongkaramasa in Gowa Regency. This study is a quantitative study with a quasi-experimental design with a nonequivalent control group design. The population in this study were all fifth grade students of SD Gugus 5, Pallangga District, Gowa Regency in the 2024/2025 academic year. The research sample was fifth grade students of SDN Borongkaramasa with a random sampling technique. The data collection technique in this study was the test and documentation technique. This study was conducted by providing a pretest as an initial result before being given treatment and at the end of the meeting a posttest was given as a result of the treatment. Furthermore, the data obtained were analyzed using the SPSS v.28 application by looking for the results of the normality test, homogeneity test and Independent Sample t-Test to test the hypothesis. Research results (1) There is an influence of differentiated learning through guided inquiry model on the problem solving ability of science subjects of class V of Borongkaramasa Elementary School in Pallangga District, Gowa Regency. (2) There is an influence of differentiated learning through guided inquiry model on the learning outcomes of science subjects of class V of Borongkaramasa Elementary School in Pallangga District, Gowa Regency. (3) It can be concluded that there is an influence of differentiated learning through guided inquiry model on the problem solving ability and learning outcomes of science subjects of class V of Borongkaramasa Elementary School in Gowa Regency.